Second International Symposium on Leveraging Applications of Formal Methods, Verification and Validation (Isola 2006) 2006
DOI: 10.1109/isola.2006.63
|View full text |Cite
|
Sign up to set email alerts
|

Static WCET Analysis of Real-Time Task-Oriented Code in Vehicle Control Systems

Abstract: Abstract. Methods for Worst-Case Execution Time (WCET) analysis have been known for some time, and recently commercial tools have emerged. This technique is gradually being entered into industry to analyse real production codes. This article presents a case study where the aiT WCET analysis tool was used to find upper time bounds for taskoriented vehicular control code. The main purpose was to investigate the practical difficulties that arise when applying the current WCET analysis methods to this particular k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…The next step is to try out the algorithms on industrial real-time codes. In a previous case study [20], we were able to obtain considerably better WCET estimates for some industrial real-time code by adding infeasible path constraints by hand. We plan to run our infeasible path analyses on the same code to see if we can derive these constraints automatically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next step is to try out the algorithms on industrial real-time codes. In a previous case study [20], we were able to obtain considerably better WCET estimates for some industrial real-time code by adding infeasible path constraints by hand. We plan to run our infeasible path analyses on the same code to see if we can derive these constraints automatically.…”
Section: Discussionmentioning
confidence: 99%
“…Recent industrial WCET case studies [3,7,20], have shown that it is important to develop good support for both loop bound and infeasible path analyses, thereby reducing the need for manual annotations.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is specifically assumed that network-on-chips can be used when the packet injection rate is low, i.e., the worst congestion does not occur. In addition, as mentioned in [38], hard real-time code often has a fairly simple control structure, with few loops, no recursion, and few dynamic features such as dynamic calls and memory allocations. Therefore, in this paper, it is assumed that the above formula is enough shorter than the deadline period.…”
Section: Deadline Constraintmentioning
confidence: 99%
“…A decade ago, Chapman [2] found that even for quite simple programs and simple hardware, 30% pessimism was not uncommon and in one case 64% pessimism was observed. More recently, an industrial case study [18] found pessimism of 4-33% when the aiT tool was used to analyse industrial code. This was approximately doubled if hand-coded annotations were not given.…”
Section: Model Inference Approach To Wcet Analysismentioning
confidence: 99%